2017
DOI: 10.1126/science.aah4886
|View full text |Cite
|
Sign up to set email alerts
|

Host cell attachment elicits posttranscriptional regulation in infecting enteropathogenic bacteria

Abstract: The mechanisms by which pathogens sense the host and respond by remodeling gene expression are poorly understood. Enteropathogenic (EPEC), the cause of severe intestinal infection, employs a type III secretion system (T3SS) to inject effector proteins into intestinal epithelial cells. These effectors subvert host cell processes to promote bacterial colonization. We show that the T3SS also functions to sense the host cell and to trigger in response posttranscriptional remodeling of gene expression in the bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(103 citation statements)
references
References 50 publications
4
95
0
4
Order By: Relevance
“…Structural studies confirmed dual-site binding (50). This general mechanism of translational repression has been substantiated for numerous E. coli mRNA targets, including csrA itself (5, 9, 11, 14, 20, 22, 23, 5255). Similar translation repression mechanisms have also been identified in several other bacterial species (31, 5659).…”
Section: Direct Csra-mediated Regulationmentioning
confidence: 85%
See 1 more Smart Citation
“…Structural studies confirmed dual-site binding (50). This general mechanism of translational repression has been substantiated for numerous E. coli mRNA targets, including csrA itself (5, 9, 11, 14, 20, 22, 23, 5255). Similar translation repression mechanisms have also been identified in several other bacterial species (31, 5659).…”
Section: Direct Csra-mediated Regulationmentioning
confidence: 85%
“…Similar translation repression mechanisms have also been identified in several other bacterial species (31, 5659). In some cases, CsrA binding sites overlap the start codon (11, 22, 23, 55, 58, 59), or initially translated region (5, 15). …”
Section: Direct Csra-mediated Regulationmentioning
confidence: 99%
“…The prophage encoded effector NleA is a critical virulence determinant of A/E pathogens (47, 48)(Fig 6). EPEC NleA expression is regulated by a post-transcriptional process where nleA mRNA is bound by the RNA binding protein CsrA to prevent its translation until T3SS-mediated host cell contact (49). CesT was further shown to relieve translation inhibition by interacting and displacing CsrA from the nleA mRNA transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of the LEE1 promoter via mechanical stress occurs independently of the mode of attachment, such as electrostatic interactions, Tir‐intimin binding, or immobilisation by antibodies (Alsharif et al, ). EPEC shows similar regulation, using the T3SS to sense the host cell and alter gene expression post‐transcriptionally to adapt to its new niche on the epithelium (Katsowich et al, ). Furthermore, the EPEC T3SS gatekeeper proteins SepL and SepD selectively mediate the secretion of translocators and effectors in response to environmental factors, including host cell attachment.…”
Section: Navigating the Gut For Colonisation And Survivalmentioning
confidence: 99%